UV-Induced Photodegradation of Naproxen Using a Nano γ-FeOOH Composite: Degradation Kinetics and Photocatalytic Mechanism - Li, Zhanyi; Liu, Guoguang; Su, Qing; Lv, Chunyan; Jin, Xiaoyu; Wen, Xiaoqing (Frontiers in Chemistry, 2019)
Naproxen (NPX) is one of the most common pharmaceutical and personal care products found in surface water, which is recalcitrant to degradation by biological treatment or complete removal via traditional sewage treatment processes. In this study, nanoscale γ-FeOOH was synthesized and characterized by X-ray diffraction, scanning electron microscopy, surface analysis, and analysis of the forbidden bandwidth. Under UV irradiation, γ-FeOOH had the capacity to rapidly photodegrade NPX. The photodegradation rate of NPX was dependent on the concentration of γ-FeOOH in solution, initial NPX concentration, and pH. By increasing the concentration of γ-FeOOH, the NPX photodegradation rate was increased and then remained stable. Furthermore, the highest photodegradation rate for NPX was observed under acidic conditions. Through the analysis of the active substances (such as h+, e-, ·OH, 1O2, and O2·-) by electron spin resonance, the photocatalytic mechanism of NPX degradation on γ-FeOOH was determined to be semiconductor photocatalysis.